2015
DOI: 10.1128/aac.01176-15
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of GlpT and UhpT via FNR Activation Contributes to Increased Fosfomycin Susceptibility in Escherichia coli under Anaerobic Conditions

Abstract: Because a shortage of new antimicrobial agents is a critical issue at present, and with the spread of multidrug-resistant (MDR) pathogens, the use of fosfomycin to treat infections is being revisited as a "last-resort option." This drug offers a particular benefit in that it is more effective against bacteria growing under oxygen-limited conditions, unlike other commonly used antimicrobials, such as fluoroquinolones and aminoglycosides. In this study, we showed that Escherichia coli strains, including enterohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Therefore, urine physiological pH values may improve the effect of FOS in these patients. Additionally, growth under anaerobic conditions has also been related to increased antibacterial activity of FOS due to elevated expression of GlpT and UhpT after activation of FNR, leading to increased FOS uptake (44). The results obtained in our study support this finding, with 2-to 32-fold MIC reductions observed under anaerobic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, urine physiological pH values may improve the effect of FOS in these patients. Additionally, growth under anaerobic conditions has also been related to increased antibacterial activity of FOS due to elevated expression of GlpT and UhpT after activation of FNR, leading to increased FOS uptake (44). The results obtained in our study support this finding, with 2-to 32-fold MIC reductions observed under anaerobic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…This drug is rather more effective under anaerobic conditions whereas most of other drugs decrease their activities ( Inouye et al, 1989 ; Bryant et al, 1992 ; Morrissey and Smith, 1994 ; Grif et al, 2001 ; Kohanski et al, 2010 ). In our previous studies on Escherichia coli , we found that FNR (Fumarate Nitrate Reduction) and CRP (cAMP receptor protein) are positive regulators of both glpT and uhpT genes, and activities of these regulators increase under anaerobic conditions, which results in increased intracellular accumulation of fosfomycin ( Kurabayashi et al, 2015b , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation assay. The accumulation assay was based on the technique described by Kurabayashi et al, with some modifications (14). S. aureus cells were grown in LB medium until an optical density at 600 nm (OD 600 ) of 0.6, were harvested and resuspended in 2 ml of LB supplemented with 10-fold the MIC of fosfomycin, and then were incubated at 37°C for 1 h. The bacteria were washed thrice with phosphatebuffered saline, resuspended in 500 l of water, boiled for 3 min, and centrifuged to collect the pellets.…”
mentioning
confidence: 99%
“…Accumulation of fosfomycin in S. aureus mutants and overexpressors. Using a previously described bioassay for bacterial cell accumulation of fosfomycin (14), we determined if the effects of tet38 and glpT on fosfomycin MICs could be correlated with drug accumulation. Fosfomycin accumulation was decreased 2-to 3-fold in the tet38 overexpressor strain and QT03 (glpT mutant) (Table 3), findings consistent with changes in fosfomycin MICs and supporting a role for Tet38 as an efflux transporter and GlpT as an uptake transporter of fosfomycin in S. aureus.…”
mentioning
confidence: 99%
See 1 more Smart Citation